Technical-tactical analysis of XXXII Summer Olympic Games and 2022 World Championship freestyle wrestling competitions - Arabaci, R.; Gungor, A. K.; Acikgoz, E. (International Journal of Wrestling Science, 2023)
PURPOSE: The aim of present study was to compare notational technical - tactical analysis of XXXII Summer Olympic Games (OG) and 2022 World Championship (WC) freestyle wrestling competitions.